Enterococcus faecium DNA in acute decompensated cirrhosis: a key player in inflammation and kidney dysfunction - Tyc, Olaf; Kraus, Nico; Wiedemann, Toska; Erasmus, Hans-Peter; Ortiz, Cristina; Vasseur, Jessica; Hourfar, Kai; Seidl, Christian; Mücke, Marcus Maximilian; Storf, Holger; Dahmer, Iulia; Herrmann, Eva; et al. (Frontiers in Medicine, 2025)
Liver cirrhosis is a major global health burden, with acute-on-chronic liver failure (ACLF) being a severe complication associated with high mortality. Systemic inflammation (SI) plays a crucial role in ACLF development, yet indicators for predicting disease progression remain limited. Enterococcus faecium (EF) has been implicated in bacterial translocation and SI, but its clinical relevance in ACLF remains unclear. We analyzed sera of 197 patients from a prospective observational study with acutely decompensated liver cirrhosis versus 234 healthy controls for the presence of EF DNA using RT-qPCR and cytokine analysis of serum samples. Overall, EF DNA was detected in 26% (n = 51, p = 0.001) of the patients, and only in 1.28% (n = 3, p = 0.001) in the control cohort. The positive patient samples were distributed as follows: 12% of patients were with stable decompensated cirrhosis (SDC), 5% of patients were with unstable decompensated cirrhosis (UDC) and 10% in patients were with ACLF. In the latter group, EF positivity significantly correlated with significant elevated leukocyte counts, increased C-reactive protein (CRP), Interleukin-6, and increased bilirubin, Aspartate Aminotransferase (AST), as well as creatinine levels. These findings suggest that the translocation of EF or its DNA, into the systemic circulation may reflect increased intestinal permeability, which is thought to be a key driver of SI and subsequent organ failure in ACLF. Taken together, our findings demonstrate that the presence of EF DNA in serum may contribute to the pathophysiological cascade of ACLF by promoting SI and organ dysfunction, particularly affecting renal function. We therefore propose and hypothesize that the presence of EF DNA in patients’ serum could serve as an indicator of intestinal barrier dysfunction and further underscores the critical role of the gut-liver axis in the development and progression of ACLF.